People living with HIV on ART have accurate perception of lipodystrophy signs: a cross-sectional study. (December 2017) - Alencastro, Paulo; Barcellos, Nemora; Wolff, Fernando; Ikeda, Maria; Schuelter-Trevisol, Fabiana; Brandão, Ajácio; Fuchs, Sandra
Abstract Background The prevalence of lipodystrophy ranges from 31 to 65%, depending on the criteria adopted for diagnosis. The usual methods applied in the diagnosis vary from self-perception, medical examination, skinfolds measurements, or even imaging assessment for confirmation of fat distribution changes. Although several methods have been developed, there is no gold standard for characterization of LA and LH, or mixed forms. This study aimed to compare self-reported signs of lipodystrophy with objective measures by skinfolds and circumferences, and to evaluate the prevalence of lipoatrophy (LA) and lipohypertrophy (LH) among subjects living with HIV/AIDS on ART. Methods A cross-sectional study enrolled participants living with HIV/AIDS receiving ART, aged 18 years or older from an outpatient health care center, in Southern Brazil. Self-reported body fat enlargement in the abdomen, chest or breasts, and dorsocervical fat pad were used to determine LH, while LA was identified by self-reported fat wasting of the face, neck, legs, arms or buttocks. Measurements were obtained with a scientific caliper for infraorbital, buccal, and submandibular skinfolds, and using an inelastic tape to measure circumferences of waist, hip, neck, and arm. LH and LA were established by the presence of at least one self-reported sign. Results Comparisons of self-reported signs with objective measurements for men and women were carried out in 815 participants on ART, out of 1240 participants with HIV infection. Self-report of decreased facial fat and sunken cheeks was associated with lower infraorbital, buccal, and submandibular skinfolds. Participants who reported buffalo hump had, on average, greater neck circumference, as well as those who have increased waist circumference also reported abdominal enlargement, but no buttock wasting. Men were most commonly affected by lipoatrophy (73 vs. 53%; P < 0.001), and women by lipohypertrophy (79 vs. 56%; P < 0.001). Conclusion In conclusion, self-reported signs of lipodystrophy and lipoatrophy are prevalent, differ by gender, and are associated with objective measurements in people living with HIV/AIDS.